Association of Obesity with Lipid Profile and Blood Pressure Among the Medical Students of Enam Medical College (Journal of Enam Medical College, 2024)
Background: Overweight and obesity are well recognized as “escalating epidemic” in both developed and developing countries. Obesity can cause many health related problems, like cardio vascular diseases (CVD). Both obesity and serum lipids are modifiable factors for CVD. Serum lipid profile of young medical students in Enam Medical College was estimated to determine their CVD risk. Objective: To find out the association of obesity with lipid profile and blood pressure. Materials and Methods: This cross-sectional analytical study was carried out at Enam Medical College, Savar, Dhaka from July 2019 − September 2019. A total of 85 apparently healthy medical students of 1st year to 5th year in Enam Medical College were included for study. Data collection sheet was prepared for the purpose of the study, which included all the variables of interest. Non-probability sampling technique was applied.  Weight, height, waist circumference and blood pressure were measured in study subjects. Association of obesity was found with body mass index, lipid profile and blood pressure. Overnight fasting (at least 12 hours) blood specimens were collected from study subjects to estimate the total cholesterol (TC), serum triglyceride, serum HDL-C. With all aseptic precautions 5 mL of venous blood was drawn from anti-cubital vein in a disposable syringe and delivered immediately into a dry clean test tube which was kept in standing position till clot formation. Then serum was separated after centrifuging at 3000 rpm for 5 minutes and collected in microcentrifuge tube, labeled properly and stored in ultrafreezer at －20ºC. All biochemical tests were done at the Department of Biochemistry of EMCH. All collected data were checked, edited and then processed with the help of the software Statistical Package for Social Sciences (SPSS) version 22.0. Results: In these studies 43 (50.6)% students were male and 42 (49.5%) students are female. The mean difference of WC, SBP, DBP, TG  between male and female patients were significant difference (p0.05). The mean of BMI and WC were statistically increased in overweight and obese student (p0.05).  In study subjects, BMI was weak positive correlation with SBP (r=+.175, p=0.109), DBP (r=+.229, p=0.035), TC (r=+.246, p=0.023), TG (r=+.145, p=0.183), LDL-C (r=+.249, p=0.022) and weak negative correlation with HDL-C (r=-.218, p=0.046). In study subjects, WC was weak positive correlation with SBP (r=+.325, p=0.001), DBP (r=+.334, p=0.002), TC (r=+.260, p=0.016), TG (r=+.180, p=0.100), LDL-C (r=+.206, p=0.058) and weak negative correlation with HDL-C (r=-.170, p=0.120). Conclusions: The epidemic of overweight and obesity is having a huge impact on the physical and social wellbeing of adult in future.  Thus, it is concluded that the parameter indicating increased cardiovascular risk such as high TC, TG, LDL-C, and low HDL-C in obese group. As TG, TC, LDL-C, showed positive correlation while HDL-C showed a negative correlation with both BMI and WC. Hence, both the anthropometric indices (i.e., BMI and WC) can be used both alone and also in combination as a predictor of abnormal lipid profile and as a cardiovascular risk also.J Enam Med Col 2022; 12(2): 68−74